Stacking Faults and Microstrains in Strain-Hardened Surface of Nitrogen-Alloyed Austenitic Steel; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Narkevich N.; Syrtanov M. S. Maksim Sergeevich; Mironov Yu.; Surikova N. (2016, 2016)
Title screen